2014
DOI: 10.1136/bmjquality.u206189.w2537
|View full text |Cite
|
Sign up to set email alerts
|

Ward round documentation in a major trauma centre: can we improve patient safety?

Abstract: Our objective was to improve documentation and patient safety in a major trauma centre.A retrospective audit was undertaken in March 2014. Ward round entries for each orthopaedic patients on three dates were assessed against standards and analysed. The audit was repeated in April 2014, and again in August 2014.Thorough documentation is paramount in a major trauma centre. It forms a useful record of the patients hospital stay, is a legal document and is highlighted in national guidelines. It provides a basis fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Additionally there is time and resource pressures on secretarial support for typing operative notes which affect the timely production of typed notes and increase the potential costs to the trust. There have been a number of quality improvement projects that have utilised the use of electronic templates [4][5][6] although none have developed a sustainable, integrated, and comprehensive electronic operative notes template.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally there is time and resource pressures on secretarial support for typing operative notes which affect the timely production of typed notes and increase the potential costs to the trust. There have been a number of quality improvement projects that have utilised the use of electronic templates [4][5][6] although none have developed a sustainable, integrated, and comprehensive electronic operative notes template.…”
Section: Introductionmentioning
confidence: 99%
“…compared to the second cycle (P=0.203) [17]. Our study showed that BOA guidelines can be followed more easily by electronic methods than paper-based and have showed significant improvement in ward round documentation.…”
Section: Discussionmentioning
confidence: 60%
“…Based on the bene ts of systematic ward rounds and checklists presented by previous research (19,20) and compliantly with national standards we have developed a ward round note that includes all mandatory information for daily patient review. Further research should explore the impact of this new documentation method on patient care and postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%